Plasmonic op-amp circuit model using the inline successive microring pumping technique - Youplao, P. (Springer Nature Switzerland AG, 2018)
The electro-optic power pumping system model using the inline successive technique within the modified add-drop filter is proposed. A pumping system consists of a closed loop Panda ring resonator, from which the optical power is coupled inline into the system. By controlling the two side phase modulators, the whispering gallery mode (WGM) is generated by the amplitude-squeezed light within the modified add-drop filter. By using the proposed circuits, the low current can be applied into the system via a gold layer connection, from which the amplified output current can be obtained at the throughput port, which can be functioned as the electronic operational amplifier (op-amp). In application, the WGM output is the amplified signal that can be used for the up (down) link in free space communication network called light fidelity (LiFi). The electro-optic signals conversion can be performed by the stacked layers of silicon–graphene–gold materials. The results obtained have shown that large gain is obtained at the WGM output, which is ~ 5 × 10-6cm2(VsW)-1, when the pumping saturation time is ~ 2 fs. It concludes the suitability of our proposed model for light fidelity, LiFi up-down link conversion.